Application of the synectics model to enhance students' writing skills through digital storytelling using kinemaster - Setiana, Leli Nisfi; Nuryatin, Agus; Supriyanto, Teguh; Setyaningsih, Nas Haryati; Maulana, Andi (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the application of the Synectics model in improving students' writing skills through digital storytelling using the Kinemaster app. The purpose of this research is to explore how integrating the Synectics model, a creative problem-solving approach, with digital tools can enhance students' writing outcomes. A qualitative descriptive methodology was employed to gather and analyze data. The findings indicate that students effectively utilized the Synectics model in combination with Kinemaster to create compelling digital stories. This approach not only strengthened their writing structure but also enhanced their creativity and engagement with the content. The study concludes that the integration of the Synectics model with digital storytelling tools can significantly improve students' writing skills by fostering creativity, critical thinking, and content presentation. Practical implications suggest that educators can adopt this innovative method to enrich writing instruction and align with the growing use of technology in education. This research offers valuable insights into modernizing writing pedagogy, making it more relevant and engaging for students in the digital age.